INTEGRASI STEM DALAM KURIKULUM MEMPERSIAPKAN GENERASI MASA DEPAN - Ridwan; Ali Ramatni; Al Ikhlas; Gusnidar; Loria Wahyuni; Dhiraj Kelly Sawlani (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The integration of STEM (Science, Technology, Engineering, and Mathematics) in the education curriculum is one of the strategic steps in preparing a generation that is adaptive to technological developments and global challenges. STEM-based education encourages students to develop critical thinking, creativity, collaboration, and problem-solving skills through an interdisciplinary approach. In the context of the curriculum, STEM implementation presents challenges in terms of syllabus adjustments, teacher training, and procurement of adequate learning facilities. However, STEM integration also offers great opportunities to create an educational ecosystem that is relevant to the needs of the 21st century workforce. This article discusses the basic concepts of STEM integration, implementation strategies in the curriculum, and its impact on students' readiness to face the industrial revolution 4.0 and a dynamic future. Based on the analysis of literature and practices in various countries, it is identified that collaboration between the government, educational institutions, and the private sector is needed to support the success of STEM integration in the education system. Thus, STEM integration is expected to be a strong foundation in building a competent, innovative and globally competitive generation.